LEMBAGA TRADISIONAL MELAYU - Fathatul Khoiriyah; Fitria Hartati; Ismail Sukardi; Nyayu Soraya (STKIP Subang, 2026)
Traditional Malay Islamic educational institutions are an important part of the history of Islam's development in the Malay-Nusantara region. The presence of institutions such as surau (Islamic prayer houses), Islamic boarding schools (pesantren), madrasahs, and mosques not only serve as centers for the transmission of Islamic knowledge but also as a means of shaping the identity, character, and culture of Malay Muslim communities. This article aims to analyze the definition, characteristics, development, and transformation of traditional Malay Islamic educational institutions in the face of modernization. This research uses library research with a descriptive-analytical approach through a review of various scientific literature, books, journals, and documents related to Malay Islamic education. The results show that traditional Malay Islamic educational institutions have distinctive characteristics, including an emphasis on moral education, the teaching of classical texts, spiritual relationships between teachers and students, and community involvement in their management. Over time, these institutions have undergone transformations in their curriculum, learning methods, and institutional systems in response to social change and the demands of modernity. This transformation has given rise to a more adaptive form of Islamic education without abandoning the basic values ​​of Malay Islamic education. Thus, traditional Malay Islamic educational institutions remain relevant as a foundation for the development of Islamic education in the contemporary era.